Molecular biology of the cell (Garland Science, 1989)
New edition of a text in which six researchers from leading institutions discuss what is known and what is yet to be understood in the field of cell biology. The material on molecular genetics has been revised and expanded so that it can be used as a stand-alone text. A new chapter covers pathogens, infection, and innate immunity. Topics include introduction to the cell, basic genetic mechanisms, methods, internal organization of the cell, and cells in their social context. The book contains color illustrations and charts; and the included CD-ROM contains dozens of video clips, animations, molecular structures, and high-resolution micrographs.